Studi Potensi Kualitas Air Wilayah Tambak dengan Sistem Informasi Geografis (SIG) di Kabupaten Sidoarjo - Farid, Akhmad (Rekayasa, 2008)
This research was done on April 2007 until ]uni 2007, with study area at 8 kecamatan in Kabupaten Sidoarjo, for the purpose of analysing water quality condition supporting tambak activities and to clasify tambak, river and beach water based onparameter used. A Geographical Information System (GIS) was used toanalize water quality parameters using Arclnfo and Arc Viewsoftware. Dissolved oxygen, ammonia, nitrate, nitrite, orthophosphate, unionised hydrogen acid, temperature, pH and salinity was measured. There was an indication of unionised hydrogen acid pollution found at tambak sampling area (0,062 - 6,059 ppm) and also at the river and beach (0,613 - 7,796 ppm). High eutrofication of orthophos phate exist in all of study areas (tambak:0,968 - 3.065, river and beach: 0,968 - 1,936 ppm) while only some study areas being polluted by ammonia (0,113 -0,159 ppm). Pond's salinity and temperature also range beyond the normal valuefor tambak activities. The classification result for tambak in Kabupaten Sidoarjo is 2,3 and 4 (lightly polluted, moderately polluted and highly polluted ) and for the river and beach all are included into highly polluted.